Censire l’esistente per creare il reale: l’origine indiana e la costruzione dei “rrom” (Altre Modernità, 2012)
This paper means to show how British Colonialism in India was made possible, and then sustained and strengthened, as much by cultural technologies of rule as it was by the more obvious and brutal modes of conquest. In fact colonialism was itself a cultural project of control. Colonial knowledge both enabled conquest and was produced by it. Cultural forms in Indian society were reconstructed and transformed by this knowledge. In the conceptual scheme which the British created to understand and to act in India they reduced vastly complex codes and their associated meanings to a few metonyms. An example of  colonial way of organizing and representing Indian social identity is offered by the British construction of Indian Gypsies. This communication is meant to explain first the logic of such an identification and then the new authority and vitality currently attained by this product of Orientalism in Romani political organizations and cultural associations.